2017
DOI: 10.1128/aac.00778-17
|View full text |Cite
|
Sign up to set email alerts
|

Subinhibitory Concentrations of Trimethoprim and Sulfamethoxazole Prevent Biofilm Formation by Acinetobacter baumannii through Inhibition of Csu Pilus Expression

Abstract: Acinetobacter baumannii is emerging as a multidrug-resistant nosocomial pathogen of increasing threat to human health worldwide. Pili are important bacterial virulence factors, playing a role in attachment to host cells and biofilm formation. The Csu pilus, which is assembled via the chaperone-usher secretion system, has been studied in A. baumannii ATCC 19606. Here we show that, in opposition to previous reports, the common laboratory strain ATCC 17978 produces Csu pili. We found that, although ATCC 17978 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 41 publications
5
45
0
Order By: Relevance
“…Additionally, we found that biofilm formation was accompanied by the formation of crosslinking pilus-like fibers for all strains (Fig. S8), which we attribute to chaperone-usher (Csu) pili, consistent with their role in Acinetobacter biofilm formation (66,67).…”
Section: A Baumannii Biofilm Formation On Stainless Steelsupporting
confidence: 69%
“…Additionally, we found that biofilm formation was accompanied by the formation of crosslinking pilus-like fibers for all strains (Fig. S8), which we attribute to chaperone-usher (Csu) pili, consistent with their role in Acinetobacter biofilm formation (66,67).…”
Section: A Baumannii Biofilm Formation On Stainless Steelsupporting
confidence: 69%
“…To test this hypothesis, transmission electron microscopy was performed on the WT, ∆mltB mutant, and complemented strains. The WT and the complemented strains presented long appendages, consistent with pili (Alvarez-Fraga et al, 2016;Moon et al, 2017) at their cell surface. The numbers of pili-like structures were drastically reduced in the ∆mltB mutant ( Fig.…”
Section: Mltb Influences Binding To Abiotic Surfaces and Epithelial Cmentioning
confidence: 85%
“…pilus expression, biofilm formation, and capsule production in response to various antibiotics [20,21]. These findings demonstrate that antibiotics can have complex effects on host-pathogen interactions that extend beyond simply inhibiting bacterial growth.…”
Section: Plos Pathogensmentioning
confidence: 85%
“…concentrations of trimethoprim and sulfamethoxazole results in inhibition of Csu pilus expression and thereby reduces biofilm formation. Therefore, trimethoprim and sulfamethoxazole may serve as a signal for A. baumannii to disperse biofilms and thereby escape antibiotic pressure [20]. Many strains of A. baumannii constitutively express a type VI secretion system (T6SS), which is employed to kill competing bacteria within the environment [46].…”
Section: Plos Pathogensmentioning
confidence: 99%